P43 Factors influencing length of chest drain insertion in children with empyema. (15th November 2017) - Osinibi, M; Sun, C; Bossley, C; Ruiz, G; Abusamra, R
Abstract : Introduction: Many factors might influence length of chest drainage (LOCD) when managing parapneumonic effusions/empyema including effusion size, septations, extent of pneumonia, presence of air leaks, pathogen virulence, fibrinolytic therapy with urokinase and local policies. UK guidelines recommend using the same fixed volumes for infants and for all children older than a year regardless of size. This preliminary retrospective survey was undertaken to determine whether there may be a signal to suggest an optimal urokinase volume based on weight which might warrant a controlled study. Objectives: To investigate clinical factors that affect length of chest drain insertion (LOCD) in children with empyema and to examine if there is an optimal urokinase dosing based on patient's weight would affect the LOCD. Methods: We conducted a retrospective review of clinical data from 52 children with empyema admitted to our centre between January 2015-December 2016. Chest drains were in place for a range of 2 to 12 days with a median of 5 days. We conducted a comparison of these data between the group of patients who required chest drain insertion for ≤5 days and those ≥5 days. We also grouped the patients into two levels of urokinase dose based on patients weight to create a frequency table and eventually to look if a certain dose is associated with a shorter LOCD. Results: The median LOCD insertion in our group was 5 days. Patients with a longer LOCD showed a trend to be younger and had a higher WCC, but this was not statistically significant. There were no statistically significant difference in the dose/kg of urokinase and LOCD. Conclusion: Our study did not show weather a certain urokinase dose based on weight would affect the LOCD. There were no other clinical indicators among our population that can predict the LOCD.